Technology dissemination methods in West and Central African semi-arid tropics - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
In general these methods comprise means to broaden the knowledge and the skills of target groups as well as to learn about potential structures and strategies of dissemination. Among the most important methods are: participatory variety selection, community-based seed systems, Integrated Soil Fertility (ISF) at Farmer Field Schools, and the Farmers for the Future program.